Couples' Unmet Need for Family Planning in Three West African Countries. Issue 3 (10th September 2014) - Pearson, Erin; Becker, Stan
Abstract : Unmet need for family planning is typically calculated for currently married women, but excluding husbands may result in misleading estimates of couples' unmet need. This study builds on previous work and proposes a method of calculating couples' unmet need for family planning based on spouses' independent fertility intentions. We analyze Demographic and Health Survey data from couples from three West African countries—Benin, Burkina Faso, and Mali. We find that fewer than half of couples having any unmet need had concordant unmet need (41–49 percent). A similar percentage of couples had wife‐only unmet need (33–40 percent). A smaller percentage had husband‐only unmet need (15–23 percent). Calculating unmet need based only on women's fertility intentions overestimates concordant unmet need. Additionally, that approximately 15–23 percent of couples have husband‐only unmet need suggests that men could be an entry point for contraceptive use for more couples than at present. To calculate husbands' unmet need, population‐based surveys should consider collecting the necessary data consistently.